Arabinoxylan oligosaccharides and polyunsaturated fatty acid effects on gut microbiota and metabolic markers in overweight individuals with signs of metabolic syndrome: A randomized cross-over trial. Issue 1 (January 2020) - Kjølbæk, Louise; Benítez-Páez, Alfonso; Gómez del Pulgar, Eva M.; Brahe, Lena K.; Liebisch, Gerhard; Matysik, Silke; Rampelli, Simone; Vermeiren, Joan; Brigidi, Patrizia; Larsen, Lesli H.; Astrup, Arne; Sanz, Yolanda
Summary: Background & aims: Gut microbiota composition is linked to obesity and metabolic syndrome. The nutrients and doses required to modulate the gut microbiota towards beneficially influence components of the metabolic syndrome are unclear. This study aimed to investigate diet-induced effects on the gut microbiota and metabolic markers in overweight individuals with indices of the metabolic syndrome. Methods: A twelve-week randomized cross-over trial was conducted with two intervention periods separated by a washout period. The dietary intakes of interest were wheat bran extract, rich in arabinoxylan oligosaccharides (AXOS) (10.4 g/d AXOS) and polyunsaturated fatty acids (PUFA) (3.6 g/d n-3 PUFA). Dietary records, fecal and blood samples, as well as anthropometric data, were collected before and after intervention. Anthropometry and gastrointestinal symptoms were evaluated weekly. Gut microbiota composition was analyzed by massive sequencing of 16S ribosomal RNA gene V3V4 amplicons. Results: Twenty-seven participants completed the study (90%). Intake of AXOS induced an expected bifidogenic effect on gut microbiota (p < 0.01) and increased butyrate-producing bacterial species as well (p < 0.05). Beta-diversity analysis indicated that the structure of the gut microbiota only changed as a result of the AXOS intervention (Permanova = 1.90, p < 0.02) and no changes in metabolic markers were observed after any of the interventions. Conclusions: AXOS intake has a bifidogenic effect and also increases butyrate producers in the gut microbiota; even though this type of dietary fiber did not modulate lipid or glucose metabolic parameters related to metabolic syndrome. Four-week PUFA intake did not induce any notable effect on the gut microbiota composition or metabolic risk markers. Registration: Registered under ClinicalTrials.gov Identifier no. NCT02215343. Clinical trial registration: Registered at https://www.clinicaltrials.gov/ (NCT02215343). Ethical committee: H-4-2014-052. The Danish Data Protection Agency: 2013-54-0522.